2008
DOI: 10.1111/j.1471-4159.2008.05545.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of Hsp27 does not influence disease in the mutant SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a chronic, adult‐onset neurodegenerative disorder characterized by the selective loss of upper and lower motor neurons, resulting in severe atrophy of muscles and death. Although the exact pathogenic mechanism of mutant superoxide dismutase 1 (SOD1) causing familial ALS is still elusive, toxic protein aggregation leading to insufficiency of chaperones is one of the main hypotheses. In this study, we investigated the effect of over‐expressing one of these chaperones, heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…In cells, however, HSPB1 overexpression did result in some protective effects against aggregate related toxicity, but it only mildly reduced ) or did not reduce (Patel et al 2005 ) mutant SOD1 aggregation. In line with these cellular data, overexpression of HSPB1 showed no (Krishnan et al 2008 ) or only a very mild (Sharp et al 2008 ) protective effect during early stages of disease in SOD-mice. Inversely, HSPB5 knockout mice show no enhanced degeneration when crossed with SOD1 mouse models (Yerbury et al 2013 ).…”
Section: Hspb Effects On Sod1 Mutantssupporting
confidence: 83%
“…In cells, however, HSPB1 overexpression did result in some protective effects against aggregate related toxicity, but it only mildly reduced ) or did not reduce (Patel et al 2005 ) mutant SOD1 aggregation. In line with these cellular data, overexpression of HSPB1 showed no (Krishnan et al 2008 ) or only a very mild (Sharp et al 2008 ) protective effect during early stages of disease in SOD-mice. Inversely, HSPB5 knockout mice show no enhanced degeneration when crossed with SOD1 mouse models (Yerbury et al 2013 ).…”
Section: Hspb Effects On Sod1 Mutantssupporting
confidence: 83%
“…This study was able to confirm the ability of Hsp27 and αB-crystallin to inhibit G93A SOD1 aggregation in vitro. Since previous studies have suggested that over-expression of chaperones is insufficient to attenuate the progression of ALS in mouse models (Krishnan et al 2008), further investigation to clarify the mechanism by which mutant SOD1 escapes the proteostatic machinery might provide clues to a possible treatment for ALS.…”
Section: Resultsmentioning
confidence: 99%
“…Samples from ALS brains are positive for HSPB1, HSPB5, and Hsp70 (Vleminckx et al 2002, Batulan et al 2003Maatkamp et al 2004), suggesting that Hsps might be connected to the pathogenesis of ALS. However, recent studies showed that ALS mice overexpressing HSPB1 did not have increased life span even though mutant SOD1 aggregates were decreased (Krishnan et al 2008;Sharp et al 2008). …”
Section: Role Of Small Heat-shock Proteins In Neurological Diseasementioning
confidence: 95%